2013
DOI: 10.1177/0956462413495670
|View full text |Cite
|
Sign up to set email alerts
|

Using urinary leucocyte esterase tests as an indicator of infection with gonorrhoea or chlamydia in asymptomatic males in a primary health care setting

Abstract: To evaluate a leucocyte esterase test as a predictor of gonorrhoea or chlamydia in asymptomatic Aboriginal males at the Central Australian Aboriginal Congress Male Clinic (Ingkintja), first-void urine samples and clinical information were collected from consecutive asymptomatic males presenting to the Ingkintja in Alice Springs between March 2008 and December 2009. Urine was tested immediately with a leucocyte esterase test dipstick and then by polymerase chain reaction for gonorrhoea and chlamydia. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Although LET showed moderate sensitivities of 46.4% and 68.4% for CT and NG, respectively, it had high specificity values of 92.0% and 91.8% and NPVs of 96.1% and 98.7%. This finding is in agreement with the results reported for the Central Australian Aboriginal population, which reported sensitivities of 60.0% and 66.7% and specificities of 94.7% and 90.7% compared with NAAT results for CT and NG detection, respectively ( 18 ). CT and NG can be accurately excluded if the LET result is negative.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although LET showed moderate sensitivities of 46.4% and 68.4% for CT and NG, respectively, it had high specificity values of 92.0% and 91.8% and NPVs of 96.1% and 98.7%. This finding is in agreement with the results reported for the Central Australian Aboriginal population, which reported sensitivities of 60.0% and 66.7% and specificities of 94.7% and 90.7% compared with NAAT results for CT and NG detection, respectively ( 18 ). CT and NG can be accurately excluded if the LET result is negative.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported LET sensitivity ranging from 45 to 100% for the detection of urogenital CT infections in men, with specificity ranging from 78% to 96% ( 16 , 17 ). Compared with the NAAT results for NG and CT detection, LET alone showed sensitivities of 66.7% and 60% and specificities of 90.7% and 94.7%, respectively, among Central Australian Aboriginal individuals ( 18 ). The variety of outcomes can be explained by differences in settings, patient groups, experimental test thresholds, and reference tests.…”
Section: Introductionmentioning
confidence: 95%
“…9,10 In asymptomatic men, urine tests to detect leukocyte esterase have a sensitivity of 66.7% for the diagnosis of gonorrhea and 60.0% for the diagnosis of chlamydia. Commercially available nucleic acid hybridization tests provide rapid detection of N. gonorrhoeae and Chlamydia trachomatis.…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%
“…Thus, ED patients continue to be overtreated with antibiotics for both N gonorrhoeae and C trachomatis [7,10]. Men infected with N gonorrhoeae and C trachomatis can have inflammatory changes in the urine including higher levels of urine leukocyte esterase [11][12][13][14][15]. Most research involving N gonorrhoeae and C trachomatis in men come from ambulatory care centers or STI clinics with fewer epidemiologic investigations occurring in the ED patients.…”
Section: Introductionmentioning
confidence: 99%